2015
DOI: 10.1097/igc.0000000000000424
|View full text |Cite
|
Sign up to set email alerts
|

Isolated Port-Site Metastases After Minimally Invasive Hysterectomy for Endometrial Cancer

Abstract: Isolated port-site metastases in the setting of endometrial cancer are associated with high rates of local control when treated with multimodality therapy including radiotherapy. Long-term disease-free outcomes in some patients suggest the potential for cure and justify aggressive local therapy. The optimal integration of surgery, chemotherapy, and radiation is unknown.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…Additionally, a case series of PSM after minimally invasive hysterectomy for endometrial cancer at MD Anderson Cancer Center demonstrated excellent response with high rates of local control following surgery and adjuvant radiotherapy (Grant et al, 2015). However, this case series was small, including only 7 patients, and there was no comparison group that received surgery without radiation.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, a case series of PSM after minimally invasive hysterectomy for endometrial cancer at MD Anderson Cancer Center demonstrated excellent response with high rates of local control following surgery and adjuvant radiotherapy (Grant et al, 2015). However, this case series was small, including only 7 patients, and there was no comparison group that received surgery without radiation.…”
Section: Discussionmentioning
confidence: 99%
“…Robot-assisted laparoscopy has altered the landscape of minimally invasive gynecologic surgery. [3][4][5] Expanded use of laparoscopic methods for different types of cancer has met with greater awareness of their potential complications.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 PSM is defined as tumor-cell implantation at the site of trocar insertion after laparoscopic resection of a malignant tumor. 5,8,9 PSM has been reported to occur at 1%-2% of all laparoscopic procedures in gynecologic surgery. 3,10 Isolated port-site metastasis (iPSM; also known as "solitary port-site metastasis") denotes tumor recurrence at trocar sites without evidence of concomitant metastasis.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations